Lifestyle Changes Reduce the Risk Factors of Osteopenia in Menopause Iranian Women - Arab 1*, Maliheh; Saraeian 2, Samaneh; Fazli 3, Ghazaleh; Ghodssi-Ghassemabadi 4, Robabeh; Kazemi 5, Seyyedeh Neda; Yousefi 3, Nasrin (Shahroud Journal of Medical Sciences, 2019)
Background: This study found a way to change the lifestyle and reduced the risk factors of osteopenia in menopause Iranian women.Methods: A cross-sectional study was designed in order to enroll 50 years or older asymptomatic women, who referred to the Imam Hossein medical center, Tehran, Iran for outpatient screening from 2013 up to 2015. A questionnaire including forty-one risk factors was completed and bone mass densitometry (BMD) was done by the DXA method. Bone density of femur and lumbar spine according to standard curves was calculated for each person and was recorded in the questionnaire as a study outcome. Data were analyzed using SPSS 17 software. Significant level was set at 0.05.Results: In the present study, 317 cases participated who had mean age of 52.46 years old. BMD revealed 237 (75%) osteopenia or osteoporosis prevalence. Age, menopause age and BMI related to the study outcomes significantly. Cost of each osteoporosis-osteopenia case in 50 years old or older women was 59 Dollars. Osteoporosisosteopenia was significantly related to age (Pvalue = 0.001) and menopause age (Pvalue = 0.003).Conclusions: It is reasonable that 75% osteopenia-osteoporosis will be found by BMD screening in 50 years or older Iranian women, especially if BMI be low and in the early menopause age.Keywords: Osteopenia, Lifestyle, Menopause, Women.